Upaya Pemerintah Indonesia dalam Meningkatkan Pariwisata Mandalika Melalui Kerangka Branding ‘Wonderful Indonesia’ - Satrio, Muhammad Arief (Indonesian Perspective, 2021)
This paper describes the Indonesian government’s efforts in developing Mandalika through the framework of the nation brand ‘Wonderful Indonesia’. This effort is a form of government commitment to make Indonesia the world’s maritime axis. If derived from the tourism sector, it can be interpreted as making the maritime tourism industry a top priority. This is manifested by the launch of 10 Priority Destinations where 8 of the 10 destinations are the maritime tourism industry, one of which is Mandalika which is located in West Nusa Tenggara. The government has made efforts to develop the 3A sector, namely accessibility, amenities and attractions. The development is managed by PT ITDC, a state-owned company engaged in the tourism sector and collaborates with foreign investors. In addition to the development of 3A, efforts were made to promote abroad as a form of public diplomacy and a form of efforts to promote the Mandalika Area in the corridor of the ‘Wonderful Indonesia’ branding.